A comprehensive numerical investigation of unsteady-state two-phase flow in gravity assisted heat pipe enclosure. (1st October 2021) - Arat, Halit; Arslan, Oguz; Ercetin, Umran; Akbulut, Abdullah
Highlights: A comprehensive experimental and numerical study was performed for TPCTs. A new combined numerical model containing two stages of TPCT has been composed as 3D . No steam was accepted in TPCT at beginning of simulation as different from literature. Experimental and numerical results were compared with each other in real-time steps. A video and thermal camera were utilized to observe the change of the steam volume. Abstract: In this study, thermal performance analysis of glass and copper two-phase closed thermosyphons ( TPCTs ) were investigated as 3D using comprehensive experimental methods and a new combined numerical model containing two stages. For this purpose, Volume of Fluid model has been used for the first 60 s, and Eulerian model has been employed after 60 s until 180 s for the first time in the literature. For the verification of this numerical analysis, the surface temperatures of TPCTs were measured at twenty different points by K-type thermocouples. The pressure change inside the pipes was measured by a vacuum manometer. A video camera was utilized to observe the change of steam and water volumes in the glass TPCT . The experimental and numerical results were also compared with each other in real-time for the first time in the literature. According to results, the numerical temperature distributions and steam volumes in TPCTs have shown a similar trend with the studies in the literature. It was observed that the maximum absolute temperature difference values in the evaporation, middle and condenser regions for TPCTs ranged from 6.81 K to 18.63 K. These values are similar to the values in the other studies. The maximum absolute temperature difference values were calculated between 12.09 K and 26.07 K for different turbulence models.